The Directional Signal Filtering by Progressive Phasing - Novacek, Z. (Radioengineering Society, 1992)
The paper deals with a method of signal filtering in the feed network of a phased array. Two alternative ways of phase control are described here. Both of them enable to set several directions of zero reception independently each other.
Keywords: phased array; directional filtering; elimination of undesired signals; beamforming